Wnt activation as a therapeutic strategy in medulloblastoma - Branavan Manoranjan (Nature Portfolio, 2020)
The Wnt molecular subgroup of medulloblastoma is associated with better prognosis than the other molecular subgroups. Here, the authors show that activating Wnt signaling impairs tumor development and improves survival in Group 3 and Group 4 medulloblastoma preclinical models.